Detection of ventricular tachycardia and fibrillation using ECG processing and intramyocardial pressure gradients. - Aubert AE; Denys BG; Ector H; De Geest H (Pacing & Clinical Electrophysiology, 1986)
The automatic termination of malignant tachyarrhythmias and of ventricular fibrillation by an implantable device requires a reliable sensing of these episodes of abnormal ECG. Therefore, we induced tachyarrhythmias and fibrillation in eleven dogs and recorded electrograms and intrainyocardial pressure. The electrograms were analyzed using the autocorrelation function and the probability density function. Intramyocardial pressure was monitored as a hemodynamic parameter. Results show that in the case of sinus rhythm, all methods are reliable, but in the case of VT and VF, electrogram processing only is insufficient. It is concluded that combined monitoring of ECG processing and a hemodynamic parameter may increase the sensitivity of an automatic tachycardia-fibrillation detection system.